ADRAO: Focusing on rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The Association for the Development of Rice Growing in West Africa (ADRAO) is a bilingual intergovernmental organization with 16 member countries. It has been part of the Consultative Group for International Agricultural Research (CGIAR) since 1986....